Tax-and-Match: Resolving Tension between State Financial Pressure and Federal Public Policy Intentions - Woodward, A. (Maine Policy Review, 1996)
How tax-and-match, a federal program designed to help states subsidize hospital care for low income patients, came into existence and how it was overexploited is recent history Mainers should pause to consider. Woodward traces Maine’s tax-and-match experience from its inception in 1991 to its repeal in 1995 and in doing so illustrates a set of larger issues related to the integrity of federal-state relations, the difficulties in developing fiscally sound health policies in a resource tight environment, and the political machinations that can lead to quick-fix solutions over long-term policy resolutions. With federal block grants looming in the future, Woodward suggests that if Maine is willing to learn from its recent tax-and-match experience, then perhaps Maine is poised to do the right thing when it comes to developing fiscally sound health policies for the future.
Keywords: Maine; healthcare financing; tax-and-match